High UV-visible photocatalytic activity of Ag3PO4 dodecahedral particles synthesized by a simple hydrothermal method - Krungchanuchat S. (2017)
© 2017 Elsevier B.V. Silver phosphate (Ag 3 PO 4 ) was successfully synthesized in the solutions with pH of 8 by a hydrothermal method at 100–200 °C and a precipitation method at room temperature (ca 32 °C) without any surfactant adding. Phase, morphology and vibrational modes of the products were characterized by XRD, FE-SEM and FTIR. Only morphology and crystalline degree were controlled by the synthetic methods and conditions. In this research, Ag 3 PO 4 was found to have the potential in photocatalytic degradation of organic rhodamine B (RhB) dye molecules. The photocatalytic activity of Ag 3 PO 4 dodecahedral particles synthesized by the 150 °C and 24 h hydrothermal reaction has the highest activity of 99.55% in decolorizing of RhB under UV light within 120 min.